Growing Spatial Overlap Between Dam-Related Flooding, Cropland and Domestic Water Points: A Water–Energy–Food Nexus Management Challenge in Malawi and Ghana - Li, Chengxiu; Yu, Weiyu; Dzodzomenyo, Mawuli; Asamoah, Moses; Kerapetse, Catherine Tlotlo; Kandel, Matt; Wright, Jim (Frontiers in Water, 2021)
In sub-Saharan Africa, land cover change, expansion of hydropower infra-structure, and increased flooding complicate country-level efforts to meet the Sustainable Development Goal on accessing clean and safe water. Water, Energy and Food (WEF) nexus approach recognise that addressing these complex challenges requires cross-sectoral analyses at multiple scales. Building on such an approach, and with special attention to the interrelationship of land cover change, dam-related flooding and access to safe water—an under-researched area—our study combined a national-level spatial analysis with local case studies in Malawi and Ghana to address three questions: 1) How far does agricultural land use conversion and water point installation bring water points into closer proximity with agriculture, consequently affecting water safety management by communities? 2) What is the changing spatial overlap between dam-mediated flooding and downstream domestic water points and how does it affect community use? And 3) How appropriate are existing spatial data sets for quantifying such changes? As a water-food nexus interaction, we found that areas of overlap between water points and cropland increased from 2000 to 2020 for both countries at national scale, but overlap extent varied greatly depending on the land cover product used. Local-scale exploration of water point installation patterns in Zomba Malawi confirmed this pattern, highlighting increasing non-governmental funding of borehole installation programmes. As a water-energy nexus interaction, we found that flooding mediated by hydropower dams increased for the White Volta Basin in Ghana, thereby increasing inundation of groundwater points. Local-scale focus group discussions revealed contaminated water sources and high risks of injury or drowning whilst fetching water during flooding. Overall, our study highlights how socio-economic drivers are bringing water points and cropland into closer proximity. Given differences between land cover products, we recommend more robust integration of existing land cover products to better monitor these phenomena.